Researching SJI - Peter Suber (2008)
Richard Poynder is requesting help in his research on Scientific Journals International. From his post to the AmSci OA Forum today: Update . See Stevan Harnad's comments: Update . See SJI's first response to Poynder's inquiries (August 19, 2008), Poynder's response to that (August 22, 2008), and SJI's second response to Poynder (August 29, 2008).